Online grooming: moves and strategies - Chiang, Emily; Grant, Tim (Language and Law / Linguagem e Direito, 2017)
Using transcripts of chatroom grooming interactions, this paper explores and evaluates the usefulness of Swales’ (1981) move analysis framework in contributing to the current understanding of online grooming processes. The framework is applied to seven transcripts of grooming interactions taken from perverted-justice:com. The paper presents 14 identified rhetorical moves used in chatroom grooming and explores the broad structures that grooming conversations take by presenting these structures as colour-coded visualisations which we have termed “move maps”. It also examines how some individual linguistic features are used to realise a single move termed “Assessing and Managing Risk”. The findings suggest that move analysis can usefully contribute in two key ways: determining communicative functions associated with ‘grooming language’ and the visualisation of variation between grooming interactions.